Virtual Reality and Arabic Language Learning: A Global Systematic Literature Review - Roby Kavin Ahmad Fawwaz Ziafia; Mohammad Ahsanuddin; Moh. Fery Fauzi; Keysha Wahyu Kinanthi; M. Alifudin Ikhsan; Mi Guangli (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2026)
Background: Virtual Reality (VR) has recently gained attention in language education. It offers interactive, immersive, and contextual learning experiences that cannot be provided by traditional learning media. Despite this growing interest, the use and development of virtual reality in Arabic language learning remains limited and severely underexplored. Research Objectives: This study aims to synthesize the current state of virtual reality as it relates to Arabic language learning. Methodology: This study was conducted using PRISMA 2020 to make a systematic literature review. Studies were collected with a range of publications from 2021 to 2025, sourced from five different databases. The studies were filtered using the built-in filter of the respective databases and screened further by the author. The methodological quality of these studies was evaluated using the Mixed Methods Appraisal Tool (MMAT). Results: Six studies met the criteria for analysis and synthesis. The limited number of articles shows that current VR-based Arabic language learning has an imited focus. Different forms of technology were deployed and designed, including self-developed tools and external sources. Participants reported clear benefits and limitations of the virtual reality utilization. Unique Contribution: This review contributes to mapping VR-based Arabic language learning media according to targeted skills, educational context, technological approaches, and methodological limitations, thereby offering a structured research agenda for future immersive Arabic language instruction. Conclusion: The review showed that virtual reality in Arabic language learning remains developmental and has yet to be utilized further. The main aspect of further development needs to be conducted in the long term and on a wider scale and range. Recommendations: Further research should deploy gamification and LLM to implement personalized learning. Future research should prioritize the implementation of rigorous, longitudinal research designs, aim to develop a broader range of language skills, and incorporate diverse educational environments and learner populations.